TEACHING THE CEFR ORIENTED PRACTICES EFFECTIVELY IN THE M.A. PROGRAM OF AN ELT DEPARTMENT IN TURKEY - İsmail Hakkı MİRİCİ; Nurdan Kavaklı (Informascope, 2017)
The Common European Framework of Reference for Languages: Learning, Teaching, Assessment (hereafter CEFR) and the related documents are the current realities of ELT professionals, mainly in Europe, as part of the practices in their field of study. Although it is labeled as "common" and "European", the CEFR is an internationally recognized framework worldwide. In this sense, this study aims to uncover whether the CEFR and the other related European documents such as the European Language Portfolio (hereafter ELP), as a course in M.A. classes, have reflected certain degree of effectiveness in relation to students' expectations. Herein, students' self-reflection forms and achievement test-retest scores were analyzed. Accordingly, the mixed method laced with both qualitative and quantitative data was implemented. The learners' test-retest scores as achievement criteria constituted the quantitative part of the study. On the other hand, the qualitative part was composed of the learners' self-reflection forms for the course and discussion-based self- assessment reports. The results of the study revealed the fact that the CEFR as an M.A course was internalized better on condition that the lecture was followed by self-study, self- reflection, discussion-based self-assessment as a part of review process and test-retest practices respectively, when applied whole and complete.